2010
DOI: 10.1136/jech.2009.104893
|View full text |Cite
|
Sign up to set email alerts
|

Marital loss, mental health and the role of perceived social support: findings from six waves of an Australian population based panel study

Abstract: Marital loss significantly decreased mental health. Increasing, or maintaining, high levels of social support has the potential to improve widowed men's mental health immediately after the death of their spouse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 35 publications
6
77
2
Order By: Relevance
“…Furthermore, HRQoL is negatively affected by increasing age and the occurrence of subjective memory problems. These findings are in line with a previous Australian population-based longitudinal study [13]. Moreover, the significant effect of living situation (transitions to living alone in private household decreased HRQoL significantly in the total sample and in women) should be interpreted with some caution since standard errors were quite high.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, HRQoL is negatively affected by increasing age and the occurrence of subjective memory problems. These findings are in line with a previous Australian population-based longitudinal study [13]. Moreover, the significant effect of living situation (transitions to living alone in private household decreased HRQoL significantly in the total sample and in women) should be interpreted with some caution since standard errors were quite high.…”
Section: Discussionsupporting
confidence: 89%
“…This holds true even after adjusting for various confounders. This seems to be implausible as, generally, women tend to invest more than men in social support, irrespective of age [1,13,18,60]. Yet, on the other side, women's high social ties over the course of life might lead to a faster compensation for the loss of social support in old age.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This would imply that women might be more careful than men the second time around (Poortman, 2007), with women having a weaker desire to marry or cohabit again than men-although it should be noted that recent findings on his and her marriage are inconsistent (see review by Carr & Springer, 2010). In addition, some research shows that the social-psychological impact of union dissolution is stronger for women than men (Willitts, Benzeval, & Stansfeld, 2004;Hewitt et al, 2012). Given this greater impact, we would also expect women to be more cautious leading to weaker preferences for cohabitation or marriage.…”
Section: The Role Of Gendermentioning
confidence: 93%
“…Bell and Lee (2006) report also that early or 'out of order' life course transitions (such as a first birth before finishing full time education or marrying) during women's early life course (up to age 27) are associated with higher levels of smoking. Last, two studies addressed changes in health over the divorce transition (Hewitt & Turrell 2011;Hewitt, Turrell & Giskes 2012). These studies found declines in mental health for both sexes upon divorce or widowhood, and smaller negative effects on physical health for men.…”
Section: Family and Health: What Is Known About The Australian Context?mentioning
confidence: 99%